2017
DOI: 10.1007/s10340-017-0831-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a genetically modified potato on a non-target aphid are outweighed by cultivar differences

Abstract: Insect–plant interactions may be unintentionally affected when introducing genetically modified (GM) crops into an agro-ecosystem. Our aim was to test the non-target effects of a late blight-resistant GM potato on Myzus persicae in greenhouse and climate room experiments and understand how position and number of R gene insertions can affect non-targets in GM events. We also aimed to compare results to baseline differences among three conventional potato varieties varying in resistance to late blight. Aphid dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…We can also conclude that A. colemani female weight and eclosion time are traits which are not sensitive to changes in the GM event, and thus might be inconclusive measurable traits for potential risk assessments of this particular GM trait. Lastly, and in congruence with our previous study (Lazebnik et al., ), results show that for the P. infestans‐ resistant potato lines, there was no influence of the inclusion of the additional R gene Rpi‐stol , on any of the non‐target insect traits measured. With respect to sustainability of GM potatoes, this additional R gene in the cultivar is predicted to create more durable resistance to P. infestans (Haesaert et al., ; Haverkort et al., ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We can also conclude that A. colemani female weight and eclosion time are traits which are not sensitive to changes in the GM event, and thus might be inconclusive measurable traits for potential risk assessments of this particular GM trait. Lastly, and in congruence with our previous study (Lazebnik et al., ), results show that for the P. infestans‐ resistant potato lines, there was no influence of the inclusion of the additional R gene Rpi‐stol , on any of the non‐target insect traits measured. With respect to sustainability of GM potatoes, this additional R gene in the cultivar is predicted to create more durable resistance to P. infestans (Haesaert et al., ; Haverkort et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…In our previous work, M. persicae was selected according to EFSA (European Food Safety Authority) guidelines as a focal species for potato crops. In a previous study, we observed that aphids may have a higher population growth on certain GM events of P. infestans ‐resistant GM‐potato and that position of the R gene insertion was a factor affecting the life‐history traits of the aphid M. persicae (Lazebnik et al., ). However, these findings were obtained for healthy plants, i.e., not infected by P. infestans .…”
Section: Introductionmentioning
confidence: 97%
“…Effects of non-insecticidal GE plants on aphids were reported for Myzus persicae Sulzer (Hemiptera: Aphididae) feeding on potato clones genetically engineered to carry resistance genes against the late blight pathogen Phytophthora infestans (Mont.) de Bary [20,21]. Transformation events with different positions of R-gene insertion in the genome influenced the aphids differently [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Among the most important ones in Central Europe are cereal aphids, e.g., Rhopalosiphum padi (Linnaeus), Sitobion avenae (Fabricius), and Metopolophium dirhodum (Walker) , all Hemiptera: Aphididae [15]. Aphids have previously been deployed to study non-target effects of non-insecticidal GE plants, including mildew-resistant wheat [16,17,18], leaf-rust-resistant wheat [19], late-blight-resistant potato [20,21,22], and nematode-resistant potato [23]. For the present study, aphids were selected as test organisms for the following reasons: (1) They are abundant in the field and amenable for testing in the laboratory; (2) Changes in aphid abundance can indicate potential impacts on the food-web, but also on the capability of the plants to cope with biotic stress; (3) Aphids feed on phloem sap and might therefore respond to changes in assimilate and protein supply and expression of regulators related to sugar signaling and amino-acid synthesis [7].…”
Section: Introductionmentioning
confidence: 99%
“…But for that purpose, risk management would have to shift from a process-based to a product-based approach of risk assessment. This has not happened because the PP ceased to be a tool of responsible risk management, but instead became a convenient excuse to postpone approval decisions by pointing out that off-target effects in the breeding process and indirect adverse effects resulting from the commercial use of GMO cannot be excluded entirely; however, the likelihood of such effects to occur often turns out to be lower in the case of GMO than with unregulated classical mutagenesis or conventional breeding due to the higher degree of precision and efficiency of advanced biotechnology, the more accurate identification of off-target effects, and the more strict monitoring requirements (Lazebnik et al, 2017; SAM and High-level Group of Scientific Advisors, 2017:58).…”
Section: Introductionmentioning
confidence: 99%